Validity and reliability of a multiple-group measurement scale for interprofessional collaboration - Reeves Scott; Kenaszchuk Chris; Nicholas David; Zwarenstein Merrick (BMC, 2010)
Abstract Background Many measurement scales for interprofessional collaboration are developed for one health professional group, typically nurses. Evaluating interprofessional collaborative relationships can benefit from employing a measurement scale suitable for multiple health provider groups, including physicians and other health professionals. To this end, the paper begins development of a new interprofessional collaboration measurement scale designed for use with nurses, physicians, and other professionals practicing in contemporary acute care settings. The paper investigates validity and reliability of data from nurses evaluating interprofessional collaboration of physicians and shows initial results for other rater/target combinations. Methods Items from a published scale originally designed for nurses were adapted to a round robin proxy report format appropriate for multiple health provider groups. Registered nurses, physicians, and allied health professionals practicing in inpatient wards/services of 15 community and academic hospitals in Toronto, Canada completed the adapted scale. Exploratory and confirmatory factor analysis of responses to the adapted scale examined dimensionality, construct and concurrent validity, and reliability of nurses' response data. Correlations between the adapted scale, the nurse-physician relations subscale of the Nursing Work Index, and the Attitudes Toward Health Care Teams Scale were calculated. Differences of mean scores on the Nursing Work Index and the interprofessional collaboration scale were compared between hospitals. Results Exploratory factor analysis revealed 3 factors in the adapted interprofessional collaboration scale - labeled Communication, Accommodation, and Isolation - which were subsequently corroborated by confirmatory factor analysis. Nurses' scale responses about physician collaboration had convergent, discriminant, and concurrent validity, and acceptable reliability. Conclusion The new scale is suitable for use with nurses assessing physicians. The scale may yield valid and reliable data from physicians and others, but measurement equivalence and other properties of the scale should be investigated before it is used with multiple health professional groups.